Literasi Qur’an: Upaya Peningkatan Kelancaran Membaca Al-Qur’an Melalui Program Sore Mengaji Di TPQ At-Taqwa Desa Gung - Aisyah, Siti; Naimi, Nadlrah (Journal of Community Sustainability, 2026)
This study aims to improve Qur'an literacy, particularly in terms of fluency in reading the Qur'an through the implementation of the Sore Mengaji program at TPQ At-Taqwa, Gung Pinto Village. The background to this activity stems from the still low ability to read the Qur'an among some students. This condition is influenced by limited study time in formal schools and the lack of intensive Qur'an learning assistance outside of school hours. Therefore, a coaching program is needed that can provide additional learning opportunities for students so that their Qur'an reading skills can develop well. The method used in this study is a qualitative descriptive approach. Data collection techniques are carried out through direct observation of learning activities, interviews with teachers and students, and documentation of program activities. The Sore Mengaji program is carried out routinely every afternoon with the guidance of Qur'an teachers using the talaqqi and tikrar methods, which focus on improving the reading of hijaiyah letters, makhraj, and the application of tajwid rules. The results of the activity show an increase in the ability of students to read the Qur'an more fluently and correctly. Furthermore, this program has also fostered students' interest in learning, discipline, and love for the Quran. Thus, the Evening Study Program has proven effective as a way to increase Quranic literacy within the At-Taqwa TPQ in Gung Pinto Village.